Gambaran Kelengkapan Dokumen Rekam Medis Pasien Rawat Inap - Adhani Windari; Anton Kristijono; Lina Umboro (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The study was conducted by doing the quantitative and qualitative analysis of the medical records document of inpatients in Semarang Hospital. The approach of the research was Retrospective approach. We used the purposive sampling in 15 inpatient ward. The research variables include all components of the reviews in the quantitative analysis and qualitative analysis. The results of the quantitative analysis shows that there are some incompleteness of medical record documents in the inpatient unit including charging documents, writer authentication, and inappropriate recording based on the regulations. From the result of the qualitative analysis, it can be concluded that there is consistency of recording the statement of diagnosis and treatment as well as recording the direction of informed consent. It require socialization to health workers who are in charge to fill the medical record documents about the importance of filling out the medical record completely and correctly, and to conduct an audit of medical records on a regular basis to improve the quality of medical record documents in the inpatient unit.